Structural Health Monitoring 2017 2017
DOI: 10.12783/shm2017/14066
|View full text |Cite
|
Sign up to set email alerts
|

Battery State of Charge Estimation using Guided Waves— Numerical Validation and Statistical Analysis

Abstract: This work presents a novel scalable and field deployable framework for estimating battery state of charge (SoC) based on pitch-catch guided wave propagation using lowprofile built-in piezoelectric transducers. A preliminary study is performed through experiments using piezoelectric disc transducers mounted on commercial lithium-ion (Li-ion) pouch batteries. Similar experiments are carried out on Multifunctional Energy Storage (MES) Composites, which are an energy-storing structural material recently developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…10 Similar work by Ladpli and coworkers has shown that an ultrasoundguided wave method can be used similarly to determine SoC and SoH. [11][12][13] While the vast majority of studies have focused on singlepoint measurements, other studies have shown the technique can also be used to map the surface of a cell and monitor the extent of these changes at various points within the cell as well as to detect the position of any defects that may be present. 14,15 The majority of studies reported thus far have cycled cells at relatively low (e.g.…”
mentioning
confidence: 98%
“…10 Similar work by Ladpli and coworkers has shown that an ultrasoundguided wave method can be used similarly to determine SoC and SoH. [11][12][13] While the vast majority of studies have focused on singlepoint measurements, other studies have shown the technique can also be used to map the surface of a cell and monitor the extent of these changes at various points within the cell as well as to detect the position of any defects that may be present. 14,15 The majority of studies reported thus far have cycled cells at relatively low (e.g.…”
mentioning
confidence: 98%